Teamwork skills : peer evaluation in mobile application (ePeers) / Noor Ismahani Hasbullah - Noor Ismahani, Hasbullah (2016)
The main propose of this project is to develop a mobile application to evaluate teamwork soft skills in group assessment based on the OBE requirements. Teamwork skill is one of the soft skills that should be strengthened among undergraduates in public university. This is because of the criticism from employers that most of the undergraduates are academically proficient but lack in soft skills. In order to overcome the problem, the higher learning institutions have introduced the Outcome-based Education (OBE) to help students to increase the soft skills. This project has gone through some phases from the analysis data phase to the testing and evaluation phase. All the phases are important to ensure the development of the project is smooth. In analysis phase, all data and information regarding peer evaluation, soft skills and OBE is being identified. This phase is crucial to ensure the well understanding about the project. In design, development and implementation phase, all the requirements to build the project is identified. The needed software and hardware should be ready for the development. The design of the project should be appropriate and align with the HCI design rules. Lastly, in result and analysis phase, one survey has been conducted. This survey is conducted to obtain the opinions and feedback from user about the project. The feedback from user shows the acceptance of the project to end-users or in other words to determine whether the project is success or not. For future work, ePeers would like to solve the limitations happened in ePeers version 1 such as provides the registration function to lecturer, leader of the group can register the group members and also enhance the generate report function and print function.